Gender-Leadership in the Ivory Tower: A Case Study of Institutions of Higher Education in Taraba State - Salama Bako; Abigail Karfe; Godswill Moses (Journal of Modern Psychology)
Objective: This study investigated Gender-Leadership in the ivory tower, a survey of higher education institutions in Taraba State, Nigeria.Methods: A descriptive survey design was adopted for the study. A simple random sampling method was used to select a sample size of 372 academic and non-academic staff for this study. The instrument used for the study was the Gender-Leadership Questionnaire (GLQ). Hypotheses were tested at 0.05 level of significance using a t-test.Results: The findings revealed no significant difference in the mean rating scores of women representations in leadership positions in Taraba State institutions of higher learning between academic and non-academic staff. Furthermore, the findings revealed no significant difference in the mean rating scores of underrepresentation of women in leadership positions in Taraba State institutions of higher learning between academic and non-academic staff. Women's representation in leadership positions is lopsided in favor of their male counterparts.Conclusion: Factors that contribute to women's underrepresentation in leadership positions include cognitive bias, uneven access to knowledge, opportunities and administrative responsibility, and societal privileges that favor the males among others.